TINGKAT KECEMASAN MASA PANDEMI COVID-19 DENGAN DISMENOREA PADA REMAJA DI PANTI ASUHAN AISYIYAH TUNTANG KABUPATEN SEMARANG - Nining Tunggal Sri Sunarti; Winarsih Winarsih (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
Anxiety levels during the COVID-19 pandemic with dysmenorrhea in adolescents at the AISYIYAH Orphanage, TUNTANG, SEMARANG REGENCY Adolescence is a period that has many problems and requires adjustment caused by changes in social expectations, roles and behavior. The COVID-19 pandemic is a challenge for adolescents in dealing with menstruation. Teenagers become uncomfortable, causing anxiety when approaching the time of menstruation and during menstruation. The anxiety experienced by adolescents in facing all these challenges cannot be separated from the incidence of dysmenorrhea which is the most common disorder in adolescents. This study used the DASS-42 questionnaire to determine the relationship between anxiety levels and dysmenorrhea. The results show p value = 0.015. This study concludes that there is a significant relationship between the level of anxiety and dysmenoea. Keywords: Level of anxiety, COVID-19 pandemic, dysmenorrhea, adolescents